Aspekty profilaktyczno-terapeutyczne zajęć muzycznych w przedszkolu = Prophylactic and therapeutic aspects of musical education in kindergarten - Kataryńczuk-Mania, Lidia; Szymajda, Agnieszka (Vilnius: Mykolas Romeris Universitetas)
The authors present the wide possibilities of using music for therapeutic purposes on the basis of the theoretical and practical assumptions of various authors and their own. Particularly noteworthy are the experimental studies presented on the basis of the innovative method in children?s music therapy "Musical mirror". According to the Authors, the substantive preparation of teachers-therapists to conduct classes with children is important.
Keywords: muzykoterapia; działalność muzyczna; "muzyczne lustro"; dziecko przedszkolne; nauczyciel-terapeuta; music therapy; musical activity; "musical mirror"; kindergarten child; teacher-therapist